2015
DOI: 10.1038/labinvest.2015.71
|View full text |Cite
|
Sign up to set email alerts
|

FBXW7 negatively regulates ENO1 expression and function in colorectal cancer

Abstract: FBXW7 (F-box and WD40 domain protein 7) is a tumor suppressor frequently inactivated in human cancers. The precise molecular mechanisms by which FBXW7 exerts antitumor activity remain under intensive investigation and are thought to relate in part to FBXW7-mediated destruction of key cancer-relevant proteins. Enolase 1 (ENO1) possesses oncogenic activity and is often overexpressed in various human cancers, besides its critical role in glycolysis. However, the detailed regulatory mechanisms of ENO1 expression r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
51
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 39 publications
5
51
0
Order By: Relevance
“…For example, pyruvate kinase M2 (PKM2) facilitates colon cancer cell migration and drug resistance via the modulation of STAT3 signal [13,14]. Alpha-enolase (ENO1) promotes cell glycolysis, growth, migration, and invasion in non-small cell lung cancer through FAK-mediated PI3K/AKT pathway [15], and ENO1 is confirmed as a novel substrate of FBXW7 in colorectal cancer [16]. Lactate dehydrogenase A (LDHA) acts as oncogenic role in prostate cancer [17].…”
Section: Discussionmentioning
confidence: 99%
“…For example, pyruvate kinase M2 (PKM2) facilitates colon cancer cell migration and drug resistance via the modulation of STAT3 signal [13,14]. Alpha-enolase (ENO1) promotes cell glycolysis, growth, migration, and invasion in non-small cell lung cancer through FAK-mediated PI3K/AKT pathway [15], and ENO1 is confirmed as a novel substrate of FBXW7 in colorectal cancer [16]. Lactate dehydrogenase A (LDHA) acts as oncogenic role in prostate cancer [17].…”
Section: Discussionmentioning
confidence: 99%
“…Further mining of these data with careful curation and robust algorithms in the future will greatly improve our understanding of this gene family, especially for those datasets with disease and normal tissue comparisons. Previous studies have reported many WD40 genes involved in different human diseases, such as cancer and neurodegenerative diseases141517373839. Studies on their biological roles in disease pathogenesis will be an important direction in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with their essential roles, many are involved in various diseases. For example, FBXW7 is a well-known tumour suppressor and is implicated in several cancers1415. TLE1 is also a well-studied tumour suppressor gene16.…”
mentioning
confidence: 99%
“…The inactivation of FBXW7 at the cellular level was shown to result in elevated p100 levels, and may therefore be interpreted as an increase in non-canonical NF-κB activity (135). Despite the fact that there is currently no evidence in the literature evaluating its involvement in IBD, some data have concluded that FBXW7 is downregulated in gastric cancer (136) and is inversely correlated with the tumor promoter ENO1 in colorectal cancer (137). In addition to TNAP and FBXW7, an assortment of other miscellaneous molecules have been shown to bind to NIK including epidermal growth factor (EGF) and its receptor (EGFR) (138), caspase death domains (139) and the protein of the proto-oncogene Cot/Tpl-2 (140), although only the effects on the canonical NF-κB pathway has been fully characterized for these additional proteins.…”
Section: Putting On the Brakes: Negative Regulation Of Non-canonical mentioning
confidence: 99%